(untitled) (Swiss Medical Weekly, 2013)
BACKGROUND: Although most experts recommend empirical antibiotic treatment, covering also atypical bacteria, for patients admitted to an intensive care unit (ICU), the data are not clear for patients admitted to a general ward. European guidelines recommend starting empirical treatment with a beta-lactam antibiotic with or without a macrolide, but the with/without is not clarified. We investigated whether the use of antibiotic coverage for atypical pathogens was guided by clinical parameters. METHODS: We retrospectively analysed 300 patients hospitalised with community-acquired pneumonia. Four parameters for possible atypical pneumonia (age <55 years, abdominal symptoms, sodium <130 mmol/l, immunosuppression) and three for pneumonia severity (pneumonia severity index [PSI], ICU admission, pO2<8 kPa (60 mm Hg) or O2saturation <90%) were defined and correlated with the probability of coverage for atypical pathogens. Correlations were calculated using the chi-square test for 2 x 2 tables. RESULTS: Patients younger than 55 years significantly more likely to receive coverage for atypical pathogens than older patients (odds ratio [OR] 2.68; 95% confidence interval [CI] 1.3–5.5, p = 0.009). In patients with a PSI >III the proportion receiving coverage for atypical bacteria was even smaller than in patients with less severe pneumonia (OR 0.77; 95% CI 0.60–0.99, p = 0.03), but no difference was found for PSI >IV compared with PSI ≤IV (OR = 1.03; 95% CI 0.61–1.74, p = 0.9). The other clinical parameters had no effect on antibiotic coverage: ICU admission (OR =1.39; 95% CI 0.87–2.4, p = 0.15); pO2>8 kPa or O2-Saturation >90% (OR 1.36; 95% CI 0.85–2.17, p = 0.19); abdominal symptoms (OR 1.06; 95% CI 0.51–2.25, p = 0.88); sodium <130 mmol/l (OR 0.63; 95% CI 0.29–1.36, p = 0.2) or immunosuppression (OR 1.007; 95% CI 0.462–44, p = 1). There was also no correlation between the number of clinical parameters present and the coverage of atypical pathogens (r = 0.48). Mortality was no different between patients in whom atypical pathogens were covered compared with those with beta-lactam therapy alone (OR 1.2; 95% CI 0.66–2.25, p = 0.43). CONCLUSION: Physicians have difficulties deciding when to cover atypical pathogens in hospitalised patients with community-acquired pneumonia. Guidelines should clarify under what circumstances combination therapy is warranted.